1990
DOI: 10.1177/088610999000500101
|View full text |Cite
|
Sign up to set email alerts
|

A Feminist Approach to Working With Homeless Women

Abstract: This article describes the application of a developmental model in work with groups of homeless women in two shelters and delineates the types of homeless women and the stages through which the women go as they develop. The women's development occurs in the context of affiliation, attachment, and relationship and moves from an emphasis on self to a reconnection to the community.Women's development takes place in the context of affiliation, attachment, and relationship (Gilligan, 1982;Miller, 1976). The authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…However, some clients are unable to participate in these programs because they may be frightened of the community experience. Moreover, since research about these models tends to focus on specific services that are found to be helpful, such as groups (Brown & Ziefert, 1990;Martin & Nayowith, 1989) or drop-in centers (Segal & Baumohl, 1985), practitioners still lack overarching principles to be used in planning care. Thus, a theoretical approach is needed that can be more universally applied.…”
Section: Definitions and Benefits Of Residential Carementioning
confidence: 99%
“…However, some clients are unable to participate in these programs because they may be frightened of the community experience. Moreover, since research about these models tends to focus on specific services that are found to be helpful, such as groups (Brown & Ziefert, 1990;Martin & Nayowith, 1989) or drop-in centers (Segal & Baumohl, 1985), practitioners still lack overarching principles to be used in planning care. Thus, a theoretical approach is needed that can be more universally applied.…”
Section: Definitions and Benefits Of Residential Carementioning
confidence: 99%
“…Homeless families arrive at the state of homelessness for different reasons. Strauch, Brown, and Ziefert (1990) divide homeless women into three categories. The first category is the chronically homeless women who have been homeless for at least one year.…”
Section: Homeless Familiesmentioning
confidence: 99%
“…With the exception of a few quantitative data bases describing services and programmatic issues at some family shelters (Barge & Norr, 1991; Jacobs, Little, & Almeida, 1991) and data specific to focused efforts, such as the information on health services collected by the national Robert Wood Johnson-Pew Memorial Trust Health Care for the Homeless Program (Wright & Weber, 1987), current information is largely limited to descriptive reports (Better Homes Foundation, 1990; Macro Systems, 1991). A small, but growing literature describes programmatic efforts specifically related to the needs of homeless women (Breton, 1984; Brown & Ziefert, 1990; D'Ercole & Struening 1990).…”
Section: Current Service Delivery Systemmentioning
confidence: 99%
“…As the growing literature on homeless mothers points out, homelessness among this population is associated with loss of financial security, severe emotional distress, and various difficulties that include health problems, substance abuse, and victimization (Bassuk & Rosenberg, 1988; Brown & Zeifert, 1990; D'Ercole & Struening, 1990). To address this range of problems, a comprehensive strategy is necessary, and among its components should be: 1) service-enriched permanent housing; 2) services addressing the special needs of poor and homeless mothers; 3) measures to prevent homelessness among precariously housed families; and 4) epidemiological and evaluative research into more effective interventions.…”
Section: Programmatic Recommendationsmentioning
confidence: 99%